THE ACCUMULATION OF HEAVY METALS IN SEDIMENTS OF THE WESTERN PART OF THE NORTH CASPIAN - E. V. Chujko; O. V. Popova (Юг России: экология, развитие, 2014)
Are represented the results of the analysis of long-term variability of the zinc, copper, lead, cadmium, manganese and nickel in sediments of the western part of the North Caspian. Article traces dynamics of mobile elements in the period from 2002 to 2009. For groups of metals identified common patterns. Zinc and copper varied in a narrow range. The greatest accumulation of these elements noted in 2003 Concentrations of lead and cadmium increased in 2005, according to the runoff, the volume of which in 2005 was the highest in the study period. Dynamics of manganese and nickel wore similar fluctuation character due to the binding feature of these elements. Marked increase in concentrations in 2003, 2005 and 2007. Found a close correlation between the average nickel and manganese in the sediments. Calculate the rate of accumulation of the bottom of the western part of the North Caspian Sea. Found that the highest accumulation in the bottom sediments of different manganese accumulation ratio of the bottom of which was 66.38. The smallest accumulation in sediments tend to zinc, the bottom rate of accumulation which was 0.26. During the study period marked areas with abnormal content of heavy metals. Such areas include land at about. hechenIsland, located in the south-western part of the North Caspian Sea, and the area west of shallow space p. Volga, have a direct influence of the main sleeve Delta. Volga